2015
DOI: 10.1016/j.expneurol.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin selectivity in organizing topographic regeneration of nociceptive afferents

Abstract: Neurotrophins represent some of the best candidates to enhance regeneration. In the current study, we investigated the effects of artemin, a member of the glial derived neurotrophic factor (GDNF) family, on sensory axon regeneration following a lumbar dorsal root injury and compared these effects with that observed after either NGF or GDNF expression in the rat spinal cord. Unlike previously published data, artemin failed to induce regeneration of large-diameter myelinated sensory afferents when expressed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…With combined treatment of both Rheb and NT-3, many more axons regenerated past the DREZ and some axons were able to penetrate to a depth of about 800 µm corresponding to lamina VIII under combined treatment (Figure 7C, (c)). Labeled axons also appeared patchy often following a tortuous course when compared to normal axons (Kelamangalath et al, 2015). Analysis of the total area occupied by regenerating axons using one-way ANOVA revealed a significant effect (p<0.05) of treatment (F (2,17) =12.15).…”
Section: Resultsmentioning
confidence: 99%
“…With combined treatment of both Rheb and NT-3, many more axons regenerated past the DREZ and some axons were able to penetrate to a depth of about 800 µm corresponding to lamina VIII under combined treatment (Figure 7C, (c)). Labeled axons also appeared patchy often following a tortuous course when compared to normal axons (Kelamangalath et al, 2015). Analysis of the total area occupied by regenerating axons using one-way ANOVA revealed a significant effect (p<0.05) of treatment (F (2,17) =12.15).…”
Section: Resultsmentioning
confidence: 99%
“…However, most of those studies applied just one of the NTFs that are upregulated following injury (7). Increasingly, studies have demonstrated that the application of multiple NTFs rather than a single one holds greater therapeutic promise (8)(9)(10)(11)(12). This is ascribed to the concept that different kinds and subtypes of neurons show distinctive dependence and response to different NTFs.…”
mentioning
confidence: 99%
“…60 These reports demonstrated the application of p75 NTR inhibition in multiple injury or pain-related CGRP expression, and afferent process extension. [71][72][73][74][75][76] In our immunocompetent prostate cancer model, the fact that neuronal p75 NTR and CGRP highly colocalize in common nociceptors suggests a role in nociceptive input, synaptic transmission, and sensitization in CIBP.…”
Section: Discussionmentioning
confidence: 80%